Resilient Networked Control of Distributed Energy Resources - Dominguez-Garcia, A. D.; Hadjicostis, C. N.; Vaidya, N. H. (IEEE journal on selected areas in communications, 2012)
This paper considers networked systems and develops distributed algorithm that is resilient against potential packet drops in the communication links between system components. We apply this algorithm to the problem of coordinating distributed energy resources (DERs) for the provision of ancillary services in electrical networks, e.g., reactive power support for voltage control. In this problem, each system component can contribute a certain amount of active and/or reactive power, bounded from above and (possibly) below by capacity constraints, and the objective is to coordinate the components so as to collectively provide a predetermined total amount of active and/or reactive power. In the algorithm we propose to address this problem, each DER maintains a set of variables and updates them through information exchange with neighboring DERs. We show that, as long as the underlying graph that describes the information exchange between components is strongly connected, and the predetermined total amount of active and/or reactive power does not violate (upper or lower) total capacity constraints, DERs can use this approach to calculate, in a distributed fashion, their fair contribution (subject to their capacity constraints). We show that the proposed algorithms reach almost surely convergence to the fair solution, even in the presence of communication link failures.